STUDY OF THE CONFIGURATION OF THE FRONTAL RECESS AND ITS RELATIONSHIP WITH FRONTAL SINUSITIS BASED ON COMPUTED TOMOGRAPHY - Loburets, A.V. (World of Medicine and Biology, 2025)
The anatomical complexity of the frontal-ethmoid region is a key factor influencing frontal sinus drainage and increasing the risk of frontal sinusitis. The identification of objective morphometric predictors can improve diagnosis, prognosis and surgical planning in frontal sinus pathology. The aim of the study was to establish the relationship between the complexity of the anatomy of the frontal recess and the presence of frontal sinusitis by analysing the index of surgical complexity and the anterior-posterior distance based on computed tomography in 120 patients (233 anatomical sides). Signs of frontal sinusitis were detected in 26.3% of cases. In the group with frontal sinusitis, the mean of the index of surgical complexity was 2.71±0.89 score, the anterior-posterior distance – 7.98±2.29 mm; in the group without frontal sinusitis – 2.59±0.71 score and 8.38±2.02 mm, respectively. Despite the absence of statistically significant differences (p>0.05), a decrease in anterior-posterior distance and an increase in the index of surgical complexity were accompanied by an increase in the frequency of inflammation. The results obtained indicate the potential prognostic value of these parameters and justify their inclusion in a comprehensive preoperative analysis.
Keywords: frontal sinusitis; International Classification of the Radiological Complexity; anterior-posterior distance; frontal sinus; computed tomography